Cross-linguistic transfer effects after phonologically based cognate therapy in a case of multilingual specific language impairment (SLI) - Kambanaros, Maria; Michaelides, Michalis P.; Grohmann, Kleanthes K. (My University, 2017)
Background: Clinicians globally recognize as exceptionally challenging the development of effective intervention practices for bi- or multilingual children with specific language impairment (SLI). Therapy in both or all of an impaired child's languages is rarely possible. An alternative is to develop treatment protocols that facilitate the transfer of therapy effects from a treated language to an untreated language. Aims: To explore whether cognates, words that share meaning and phonological features across languages, could be used to boost lexical retrieval in the context of multilingual SLI. This is dependent on exploiting the phonological information in the one, trained language as a mechanism for (phonological) language transfer to the other, untrained languages. Methods & Procedures: The participant is an 8.5-year-old girl diagnosed with SLI who showed a severe naming deficit in her three spoken languages (Bulgarian, English and Greek). She received training on cognates (n = 20) using a picture-based naming task in English only, three times a week, over a 4-week period for 20 min each time. Phonological-based naming therapy was carried out using form-based strategies. Outcomes & Results: There was a significant improvement during therapy and immediately after intervention on cognate performance in English which was maintained 1 month after intervention. Cognate production in Bulgarian and Greek also improved during all stages of the intervention. Improvement in the non-treated languages was slightly more than half of the improvement recorded in English. The findings reflected some degree of cross-linguistic transfer effects. Conclusions & Implications: Cross-linguistic transfer effects were evident during therapy and after therapy had finished and the effects were maintained 1 month post-treatment. Both the native language (Bulgarian) and the dominant language (Greek) benefitted equally from the treatment of cognates in English. Generalization to non-treatment words was evident, predominantly for English. The results suggest that cognates can indeed be used successfully as a WFD intervention strategy for multilingual children with SLI with lasting effects.
Keywords: Generalization; Language-non-selective account; Non-identical triple cognates